DIFFERENCES OF CORRELATION INDICES RHEOVASOGRAPHY OF HIP AND SHIN WITH ANTHROPO-SOMATOMETRIC PARAMETERS IN HEALTHY BOYS OF PODILLYA WITH DIFFERENT SOMATOTYPES - Височанський, О.В. (World of Medicine and Biology, 2015)
Aim of our work - to determine differences in performance links rheovasography of thigh and shin with anthropometric indices in healthy urban adolescents of different Somatotypes.Materials and methodsFor the study were selected 103 practically healthy boys, in the third generation residents of Podolsk region of Ukraine. Anthropometric survey of adolescents was conducted in accordance with the scheme of Bunak; somatotype determination by the method of J. Carter and B. Heath. Established next somatotypes distribution among the studied boys: mesomorph - 32; ectomorph - 33; ectomesomorph - 35.Rheovasography hips parameters determined by computer diagnostic complex, which provides simultaneous registration of ECG, phonocardiograms, basic and differential tetrapolar rheogram and blood pressure measurement. We determined the basic impedance, length of the ascending and descending parts of rheovasography, duration of fast and slow blood supply; notch amplitude, rapid blood filling, diastolic and systolic wave; dicrotic and diastolic indices; average speed of fast and slow blood supply; indicators tone of arteries of various sizes and ratios tone of arteries.Statistical analysis of the results conducted in statistical package license "STATISTICA 6.0" using nonparametric methods. Analysis of correlation obtained results was performed using the statistical method of Spearman.Results. DiscussionsEstablished substantial differences significant association indicators rheovasography of thigh and shin with anthropometric indicators by their number, direction, absence and availability. In boys mesomorph recorded the largest number of reliable communication between derivatives indicators rheovasography of hip and distal epiphysis width; between derivatives indicators rheovasography of shin and cross body size, thickness of skin and fat folds. In boys ectomorph and ecto-mesomorph established mainly significant reverse relationships between rheovasography indicators of hip and reliable direct connections between most of the rheovasography indicators of shin with almost all anthropometric parameters.In boys mesomorph set opposite reliable connections between derivatives indices of rheovasography and half covering size and muscle weight (for dicrotic index): for hips straight and for shin - inverse. In boys ectomorph set opposite reliable connections between amplitude parameters of rheovasography and preferably all anthropometric indicators: mostly reverse for hip and straight for shin. In boys ecto-mesomorph set opposite reliable connections between amplitude parameters of rheovasography and preferably totally, transverse, and covering size, thickness of skin and fat folds and fat body mass, mostly for hip reverse, and to shin - straight.Taking into account these differences allows for early detection of pathology and differential diagnosis of various diseases, receive comparable results while conducting researches in the dynamics of treatment and monitoring the effectiveness of a treatment.
Keywords: rheovasography; correlation; boys; shin; thigh